Public discourse and wilful incommensurability: a case for attentive free speech - Smith, Todd; Kelly, Benjamin W. (Frontiers in Sociology, 2024)
Many thinkers lament the decline of liberal democracy. Some argue that, to rejuvenate it, we must think big. Thinking big involves generating new ideas about how to achieve an unprecedented level of social transformation aimed at cultivating solidarity, empowering citizen efficacy, and promoting the common good. We propose that fundamental to such a transformation must be a radical change in how people speak to one another. To this end, the primary objective of this paper is to offer a framework for understanding how speech currently erodes democratic engagement. The central idea is that much of speech today both reflects and perpetuates a culture of wilful incommensurability. The core features of this culture are totalizing safetyism, expressive safetyism, dismissive intransigence, and polarized alienation, all of which have been worsened by the current trajectory of social media. The result is that people are increasingly prone to engage in degraded free speech, which is characterized by a pervasive aversion to reach out, identify points of unity, benefit from diverse perspectives, and discover truth in all its potential complexity. In view of this diagnosis and the response of those who advocate for freedom of speech, a second objective of this paper is to introduce the concept of attentive free speech. Attentive free speech has similarities with civil discourse but is specifically characterized by discernment and thoughtfulness and is imbued with key dispositions such as courage, reverence, and love. We end by inviting future research into how such speech can promote the social and spiritual health of the public sphere and freedom itself at a practical level.